A rainbow of acridinium chemiluminescence. (9th March 2021) - Best, Quinn A.; Haack, Richard A.; Swift, Kerry M.; Bax, Brian M.; Tetin, Sergey Y.; Hershberger, Stefan J.
Abstract: Multicolor chemiluminescent acridinium derivatives were synthesized by attaching various common fluorophores to the N 10 ‐acridinium position through a piperazine linker. Triggering of each acridinium derivative using alkaline hydrogen peroxide resulted in a chemiluminescence spectrum dominated by a strong emission (>95%) from the attached fluorophore. The highly quenched emission from the triggered acridinium, acting as a donor, points to a highly efficient intramolecular energy transfer in acridinium‐based chemiluminophore‐fluorophore tandems. A variable, and in many cases minimal, spectral overlap between the donor emission and the acceptor absorption may indicate that in such tandems the energy transfer follows the Dexter electron exchange mechanism. Moreover, fluorophores affixed through the acridinium 9‐position produce a typical acridinium emission profile, demonstrating the need for close distances and favorable intramolecular orientation of the donor and acceptor moieties for the energy transfer to occur. A family of red‐shifted chemiluminescent labels, all sharing a uniform triggering method, will find immediate application in multicolor ligand‐receptor assays. Along with the multiplexing capabilities, the red‐shifted chemiluminescent detection offers a higher tolerance to green‐colored biological interferences and will therefore benefit many screening and diagnostic clinical tests. Abstract : A rainbow of colors can be generated by attaching acridinium to common fluorophores, in which the resulting chemiluminescence is dominated by strong emission from the corresponding fluorophore. Highly efficient intramolecular energy transfer was observed in systems in which spectral overlap between the donor and acceptor was minimal, suggesting that the energy transfer follows a Dexter electron exchange mechanism.